Kultura ravnodušnosti: problem fluidnosti morala / The Culture of Indifference: the Problem of Moral Fluidity (Pregled: časopis za društvena pitanja / Periodical for social issues, 2026)
This paper explores the phenomenon of the culture of indifference and the problem of moral fluidity in contemporary society. The theoretical framework is primarily based on the work of Zygmunt Bauman, complemented by insights from other relevant authors such as Hannah Arendt, Émile Durkheim, and Byung-Chul Han. Methodologically, the paper relies on qualitative analysis and interpretation of theoretical sources, applying a critical-comparative approach that connects classical and contemporary sociological and philosophical perspectives. The findings show that morality in liquid modernity loses its stable foundations and transforms into “fluid morality,” marked by subjectivity, superficiality, and fragmentation. In this context, indifference does not stem merely from a lack of empathy, but rather from systemic pressure, emotional exhaustion, and the normalization of alienation. The paper concludes that the culture of indifference is one of the defining features of contemporary society and that moral renewal requires a return to an ethic of responsibility and sensitivity to the Other.
Keywords: banality; empathy; fluidity; indifference culture; morality; responsibility; moral blindness